Breaking Through Bottlenecks for Thermally Conductive Polymer Composites: A Perspective for Intrinsic Thermal Conductivity, Interfacial Thermal Resistance and Theoretics - Gu, Junwei; Ruan, Kunpeng (Nano-Micro Letters, 2021)
Rapid development of energy, electrical and electronic technologies has put forward higher requirements for the thermal conductivities of polymers and their composites. However, the thermal conductivity coefficient (λ) values of prepared thermally conductive polymer composites are still difficult to achieve expectations, which has become the bottleneck in the fields of thermally conductive polymer composites. Aimed at that, based on the accumulation of the previous research works by related researchers and our research group, this paper proposes three possible directions for breaking through the bottlenecks: (1) preparing and synthesizing intrinsically thermally conductive polymers, (2) reducing the interfacial thermal resistance in thermally conductive polymer composites, and (3) establishing suitable thermal conduction models and studying inner thermal conduction mechanism to guide experimental optimization. Also, the future development trends of the three above-mentioned directions are foreseen, hoping to provide certain basis and guidance for the preparation, researches and development of thermally conductive polymers and their composites. Highlights: 1 Bottlenecks in the field of thermally conductive polymer composites are raised, and corresponding reasons are analysed. 2 Three possible directions for breaking through such bottlenecks are put forward, and current advances in these three directions are illustrated. 3 Future development trends and demands are foreseen to help the development of thermally conductive polymers and their composites.